2015
DOI: 10.1016/j.susc.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Iridium–silicide nanowires on Si(110) surface

Abstract: a b s t r a c tWe studied physical and electronic properties of iridium silicide nanowires grown on the Si(110) surface with the help of scanning tunneling microscopy and spectroscopy. The nanowires grow along the [001] direction with an average length of about 100 nm. They have a band gap of~0.5 eV and their electronic properties show similarities with the iridium silicide ring clusters formed on Ir modified Si(111) surface.© 2015 Elsevier B.V. All rights reserved.Ir (Iridium)-silicides have the lowest (highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Despite the considerable attention for the 5d transition metal (Au, Pt, and Ir) induced NWs on Ge(001) [3][4][5][6]20], not much attention has been yet paid to the deposition of the these 5d transition metals on Ge(110). During the last decade several reports on the deposition of Dy, Co, Ag, Au, Pt, Gd, Y, Mn, Fe and Ir on the closely related Si(110) surface have appeared [21][22][23][24][25][26][27][28][29][30][31][32]. Visikovskiy and co-authors studied the Pt/Si(110) system and they found four different NW phases for coverages smaller than one monolayer (1 ML) [25], while for more than 1 ML Pt they reported the formation of 3D silicides [26].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the considerable attention for the 5d transition metal (Au, Pt, and Ir) induced NWs on Ge(001) [3][4][5][6]20], not much attention has been yet paid to the deposition of the these 5d transition metals on Ge(110). During the last decade several reports on the deposition of Dy, Co, Ag, Au, Pt, Gd, Y, Mn, Fe and Ir on the closely related Si(110) surface have appeared [21][22][23][24][25][26][27][28][29][30][31][32]. Visikovskiy and co-authors studied the Pt/Si(110) system and they found four different NW phases for coverages smaller than one monolayer (1 ML) [25], while for more than 1 ML Pt they reported the formation of 3D silicides [26].…”
Section: Introductionmentioning
confidence: 99%
“…Ir (iridium) has already been shown to form nanowires on Ge (001), Si (001), and Si (110) surfaces. [20][21][22] In this paper, we report Scanning Tunneling Microscopy/ Spectroscopy (STM/STS) data to reveal electronic properties of Ir-silicide nanowires alongside with ab-initio density functional theory (DFT) calculations to explain the origins of these electronic properties and the structure of Ir-silicide nanowires.…”
Section: Introductionmentioning
confidence: 99%